Penggunaan Jamur Endofit untuk Mengendalikan Fusarium oxysporum f.sp. capsici dan Alternaria solani Secara in Vitro - Amalia Tri Kurnia; Mukhtar Iskandar Pinem; Syahrial Oemry (Universitas Sumatera Utara, 2014)
Using of endophytic fungi to control Fusarium oxysporum f.sp. capsici and Alternaria solani invitro. This research aimed to know efectivity of endophytic fungi to control F. oxysporum f.sp.capsici and A. solani in vitro. This research was conducted on Plant Disease Laboratory, Faculty ofAgriculture, University of North Sumatera, used Randomized Complete Design with two factors intwo replicates. First factor was kind of pathogen (F. oxysporum f.sp. capsici and A.solani). Secondfactor was kind of endophytic (E1, E2, E3, E4, E5, E6, E7, E8, E9, E10, E11, E12, E13, E14 andE15). The result showed that kind of phatogen, kind of endophytic and interaction between them sosignificantly effect on inhibiting zone, growth width of colony and diameter of colony. The bestresult was showed on E6 and E3 to control F. oxysporum and A. solani with 56.89% and 54.10 %inhibiting zone.Key words: endophytic fungi, F.oxysporum, A. solani.